Clinical comparison of Pulsair non-contact tonometer and Goldmann applanation tonometer in Indian population - Shalini Mohan; Satyaprakash Tiwari; Arvind Jain; Jaya Gupta; Surendra Kumar Sachan (Journal of Optometry, 2014)
Introduction: Goldmann applanation tonometer (GAT) is the gold standard for Intraocular Pressure (IOP) measurement but has disadvantage of being contact device and problems with portability. The aim of the study was to compare the Keeler's Pulsair noncontact tonometer (NCT) with GAT in Indian Population. Materials and methods: Eighty-one subjects were screened from a Glaucoma clinic of a tertiary care centre in North India. The IOP was measured by Pulsair NCT and GAT after explaining the procedure. Central corneal thickness (CCT) was measured to avoid its bias on IOP readings. The data were analyzed using SPSS software. Results: The mean age of subjects was 49.9 ± 8.8 (mean ± SD) years. The mean IOP as taken by Pulsair NCT was 15.79 ± 4.07 mmHg and that for GAT was 17.02 ± 4.23 mmHg (p = 0.062). The mean CCT was 0.536 ± 0.019 mm. A positive Pearson's correlation coefficient of 0.909 (p = 0.0001) was found between the two instruments. Bland and Altmann analysis showed a fair agreement between the two tonometers at lower IOP range. Conclusion: Pulsair NCT can be used as a screening tool for community practices but is not reliable in the subjects with higher IOP range.